Mechanisms and therapeutic targets for neuropathic itch - Pereira, Manuel P.; Schmelz, Martin; Ständer, Sonja (Current opinion in neurobiology, 2022)
Neuropathic pruritus conditions arise from structural and/or functional damage of the peripheral or central nervous system. Novel findings of pruritus specific mediators and pathways strengthen the specificity theory of pruritus transmission, however electrophysiological studies suggest that focal activation of nociceptors and distinct discharge patterns of primary afferents also contribute to the development of the sensation of pruritus. A complex interplay between excitatory and inhibitory interneurons at spinal level, non-neuronal cells and descending modulation from upper centers contributes to neuronal sensitization and clinically to the chronicity of pruritus, as well as accompanying phenomena such as alloknesis and hyperknesis. Several topical, systemic and non-pharmacological therapeutic approaches directed at distinct targets are currently available.
Gesehen am 04.08.2022